PERENCANAAN ULANG SITE JARINGAN GSM 900 DAN 1800 DI KOTA SEMARANG - Sukiswo, Sukiswo (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
Global System for Mobile Communication (GSM) is designed to provide solutions for high increasing number of subscribers of mobile communication services, while the frequency resources is limited. GSM is a digital cellular communication technology with a coverage service area is divided into small areas called cells, and each cell is handled by a site. To anticipate the growth of users number GSM system requires site re-planning that consist of three aspects, namely capacity, coverage and quality. With this site re-planning the number of site eficiency is expected. This paper has made simulation re-planning for an outdoor coverage site system of GSM radio network 900 and 1800 in Semarang city, which has area of 373.67 km2 and consists of 16 districts and 177 villages, so it can serve customers until 2014. From re-planning simulation for GSM 900 and 1800 radio network outdoor site coverage system in Semarang,can be known the needed number of sites to serve the customers until the year 2014 with a teledensity of 30%, i.e 91 sites with 250 Global System for Mobile Communication (GSM) sectoral cells and 230 Digital Cellular System (DCS) sectoral cells with the highest traffic for the micro cells occurred at sector 3, Sendangguwo village, District Tembalang that is equal to 132.36 Erlang, while the highest traffic for the macro cells occurred in Sector 3 Bamban Kerep village, District Ngaliyan which amounted to 66,24 E. Keywords: Re-planning, site, GSM, coverage, Semarang City